1993
DOI: 10.1093/rheumatology/32.8.693
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Sacroilhtis in Beh Disease

Abstract: Radiographs of the sacroiliac joints of 34 patients with Behçet's disease were read blind by a senior radiologist. They were compared with those from 25 controls, 14 of whom were healthy. The remainder (11) had other rheumatological disorders including six who had AS. One patient with Behçet's disease had radiologically proven sacroiliitis only but her history was atypical and she was B27 positive. All patients with AS had definite sacroiliitis. Five out of 34 patients with Behçet's disease and four of 25 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 0 publications
0
15
1
2
Order By: Relevance
“…There could be no difficulty in interpreting SI in patients with moderate or advanced SI. Major problem existed in minimal SI or lower grades of SI (2,21). The current study showed that the frequency of SI in BD group was slightly increased without statistical significance when compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…There could be no difficulty in interpreting SI in patients with moderate or advanced SI. Major problem existed in minimal SI or lower grades of SI (2,21). The current study showed that the frequency of SI in BD group was slightly increased without statistical significance when compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, several patients with coexisting AS and BD have been described in the literature (11,(16)(17)(18)(19). However, other authors have found that the prevalence of AS or SI in BD has not been different from that in the general population (20)(21)(22)(23)(24). Although Dilsen et al reported the highest level of 33 (10%) patients with AS and 112 (34%) with SI among 334 Turkish patients with BD (13), other authors found no evidence of an increased frequency of SI in patients with BD and described only one patient with definitive AS among 114 patients with BD in the same population (20).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of sacroiliitis in Behget's disease has been subject to debate but probably it is not more frequently encountered than in the general population [19]. It has also been claimed that observer variations might have caused an overestimation of sacroiliitis in FMF and Beh~et's disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…The involved joints included knee joints, sternoclavicular joints, the wrist, foot, and tarsal scaphoid, whereas the spine or sacroiliac joint was not afected. On the other hand, sacroiliitis and enthesitis have been reported in BD, although their prevalence is low [17,18].…”
Section: Atypical Joint Involvement: Destructive Arthritismentioning
confidence: 99%